2022
DOI: 10.3389/fbioe.2022.1106267
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in wound management: Tailoring superwettable bio-interfaces

Abstract: Skin tissue suffering from severe damages fail in self-regeneration. Proper wound dressings are highly demanded to protect the wound region and accelerate the healing process. Although large efforts have been devoted, there still exist disturbing dilemmas for traditional dressings. The exquisite design of bio-interface upon superwettable materials opens new avenues and addresses the problems perfectly. However, the advancements in this area have rarely been combed. In light of this, this minireview attempts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…Предполагалось, что повязки, сохраняющие влажность раневого ложа, должны улучшать санацию и ускорять заживление хронических ран [24][25][26][27]. Однако до сих пор нет убедительных доказательств, что модернизированные повязки более эффективно ускоряют заживление хронических ран, чем обычная марля с раствором натрия хлорида (пищевой соли) [28][29][30][31].…”
Section: особенности традиционной терапии хронических ранunclassified
See 1 more Smart Citation
“…Предполагалось, что повязки, сохраняющие влажность раневого ложа, должны улучшать санацию и ускорять заживление хронических ран [24][25][26][27]. Однако до сих пор нет убедительных доказательств, что модернизированные повязки более эффективно ускоряют заживление хронических ран, чем обычная марля с раствором натрия хлорида (пищевой соли) [28][29][30][31].…”
Section: особенности традиционной терапии хронических ранunclassified
“…Сложившаяся практика лечения хронической раны заключается в закрытии ее поверхности раневой повязкой на срок около суток, после чего «грязную» раневую повязку удаляют, рану открывают на 10-15 мин, в этот период рану обрабатывают моющими, антисептическими и/или химиотерапевтическими лекарственными препаратами, а затем вновь закрывают свежей (чистой) раневой повязкой [25]. Чаще всего обновление раневых повязок осуществляется ежедневно, а открытая раневая поверхность орошается кипяченой водой, 0,9 % раствором натрия хлорида (солевым раствором), растворами традиционных моющих средств, локальных антисептиков и/или химиотерапевтических лекарственных средств [27]. При этом основной целью лекарственной санации хронических ран традиционно является обеззараживание, а не растворение гнойно-некротических масс [45].…”
Section: антисептические пиолитики как альтернатива личинкам мясной мухиunclassified
“…However, during our clinical practice, we found that, in our patients who received the ESPB during the posterior spinal operation for spinal fusion or decompression, although they had improved pain relief and consumed less amount of anesthetics, they also had an excessive amount of exudate from the surgical wound after the operation. During the wound healing process, the appropriate amount of exudate can provide a moist environment to promote wound healing, whereas over-production of exudate at the surgical site could cause patient discomfort, delay the wound healing process, and increase the risk of infection [ [10] , [11] , [12] ]. We found no prior research on wound exudate and its management following the ESPB procedure during posterior spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] However, excessive wound exudate during inflammation can create an ideal microenvironment for bacterial breeding and potential infections because the exudate is nutrient-rich containing many vitamins, growth factors, and leukocytes. [8,9] Traditional hydrophilic wound dressings (e.g., gauzes, bandages, and hydrogels) integrated with antibiotic substances partially improved wound healing by absorbing excessive exudate and inhibiting bacterial growth. [1,6,7,9,10] Even the emerging Janus membranes with a hydrophobic-hydrophilic interface (e.g., fiber-, sponge-, hydrogel-, and polymerbased dressings with asymmetric wettability) accelerated drainage of excessive biofluid around wounds through unidirectional water-transfer capability from the skin-facing hydrophobic side to the exposed hydrophilic side while preventing favorable conditions for bacterial growth.…”
Section: Introductionmentioning
confidence: 99%